Mindful Consumption: Investigating the Role of Environmental Risk Perception and Green Advertising on Thai Consumers’ Green Purchasing Intentions - Sombultawee, Kedwadee (Thammasat Review, 2026)
This study investigated the role of environmental perceptions and cognitions and green advertising on the purchase intentions of Thai consumers, using the stimulus-organism-response approach. Green risk perception (the perceived risk of environmental damage and climate change) and green advertising were positioned as stimuli, with environmental concern (awareness of and concern for environmental issues) and green attitude (willingness to act on environmental concern) as organism processes and purchase intention for green goods as response. Data was collected using an online survey of Thai consumers (n = 450) and analyzed using descriptive statistics and ordinary least squares regression. Results showed significant positive effects of environmental risk perception and green advertising on environmental concern and green attitude. Environmental concern and green attitude had significant positive effect on purchase intention for green goods. The research addressed a gap in understanding of external stimuli like environmental risk perception and green advertising on consumer cognitions and behavior. The study’s findings suggest these external stimuli may be more important than previously thought in influencing purchase intentions, which has implications for both theory and for marketing practice.